Efektivitas Layanan Konseling Kelompok Dengan Teknik Homework Assignment Untuk Meningkatkan Tanggungjawab Belajar - Safira, Nabila Atari; Siregar, Alfin (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2024)
This research aims to analyze the effectiveness of group counseling services using the Homework Assignment technique approach to increase student learning responsibility at SMA Negeri 7 Medan. This research used quantitative experimental methods. This research involved 56 class X students and a sample of 8 people who were selected using purposive sampling. The research design uses pre-experiment pretest-posttest. The results of data analysis using the Wilcoxon Signed Ranks test showed asymp significance. sig (2-tailed) of 0.012 is lower than the specified significance level (0.05). Thus, the Homework Assignment technique through counseling services has proven to be effective in increasing student learning responsibility